Research of technological processes of manufacture of legs of dining tables of various designs - Gayda, S.V.; Voytovych, I.G.; Orikhovskyy, R.Ya. (Forestry, Forest, Paper and Woodworking Industry, 2020)
A technical description of the legs of dining tables of various designs with the texture of oak wood with the following dimensions of 750 × 52 × 52 mm. A method for studying the production processes of production of dining table legs of various designs with the texture of oak wood. Necessary materials have been calculated to make three types of dining table legs with oak wood texture. The necessary equipment has been calculated and the routes of technological processes have been developed and the planning of the shops has been presented in order to make three varieties of modern dining table legs with oak wood texture. The comparison of technological processes of making dining table legs with the texture of oak wood is made. You have determined the rational technological process of making the legs of dining tables. It is estimated that the third option for making dining table legs with a wood texture of square cross-section is optimal, where the cost of equipment is 817.25 thousand UAH, the number of employees 10 people, total power is 34.8 kW. It should also be noted that the third option generates the least wood waste and residues, in particular in the amount of 103.37 m3, and the cost of materials for a set of legs in the amount of 4 pieces is the lowest, amounting to UAH 312, which is much less than other options. The highest value of economic efficiency is the third option of investment, which is 0.208. The payback period for this option is 4.8 years. Therefore, the technology of making dining table legs is recommended, in which the base is made of three laminated rails with chipboard with a thickness of 16 mm with a square cross section of 48 (16 × 3) × 48 mm, and the shank with a cross section of legs made of planed oak veneer with a thickness of 2 mm.